O entre da liberdade, as prisões: Os feminismos que emancipam, prendem? Uma história do gênero feminino na Penitenciária Regional Feminina de Campina Grande (1970-2000) - Silva, Vanuza Souza (2014)
This research although done in the present day, discusses the historical processes of social changes since the 60s, 70s and 80s and of the twentieth century about the place of women from the feminist movement in the streets, in academics which claim the entry of women into the job market and questioning the idea of the woman only as a symbol of motherhood and marriage. This research shows that the impacts of feminism were experienced differently by women in poor neighbourhoods. - This paper is a discussion of the involvement of women in different crimes. With this research we realized that they are predominantly illiterate or semi - illiterate women who are outside the job market and women with no professional expertise, moreover, in most cases, are part of families where they were raised by single mothers, who took to the streets to work, and others were involved with drugs. Their fathers are a great absence in the lives of these women. These female prisoners also reproduce the type of the families in which they were born, single mothers, women who had more than one relationship and children with different fathers, are also predominant among these imprisoned women. Involvement with drugs is related to a search for basic needs such as food for some, for others it means having access to fashionable clothes, and others by peer pressure, as with the majority of women involved in drug trafficking.These women question on one side, the docile, passive e woman, when choosing to use force and violence to assert themselves, but at the same time they reinforce their masculinity. These women produce multiple personalities, docile, submissive, aggressive subjectivities, construct different bodies, bodies that rebel in death, in madness, bodies that recreate their own aesthetic with piercings, bodies that also get deformed. Within prisons these women in their letters return to the values questioned, write themselves as maternal, docile, the act as the daughters they were not , the mothers they are not and make romantic love a chance for self-assertion , a yes to life in prison . Captured women dramatize different ways the for the place of women in the streets, in prisons, on one side they questioned the traditional values of women in prison, the return to their mother's place, romantic love, they question the place of the masculinity to use force and violence in the streets, reinforced with violence and all learning of the macho, masculine culture. This is a story of the infamous lives, a narrative that chose the prison to discuss the trajectories of females, inspired by poststructuralist Michel Foucault, Gilles Deleuze, Gilles Lipovetsky and Judith Butles which build discussions on the processes of subjectivity in a societies discipline, control and legitimizing the capitalist system to capture women’s work market, for the fashion and beauty industry .. This work is also inspired by Roland Barthes and Blanchot Marucie discussing writing as performance. The inmates are featured in the context of changes in which women's emancipation means to other prisons.